2012
DOI: 10.1007/s00429-012-0431-4
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-132: a dynamic regulator of cognitive capacity

Abstract: Within the central nervous system, microRNAs have emerged as important effectors of an array of developmental, physiological, and cognitive processes. Along these lines, the CREB-regulated microRNA miR-132 has been shown to influence neuronal maturation via its effects on dendritic arborization and spinogenesis. In the mature nervous system, dysregulation of miR-132 has been suggested to play a role in a number of neurocognitive disorders characterized by aberrant synaptogenesis. However, little is known about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
140
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(146 citation statements)
references
References 83 publications
(117 reference statements)
5
140
1
Order By: Relevance
“…Mir-132 levels in the hippocampal formation are also increased by other behavioural tasks, such as the Barnes maze or novel object recognition [62], suggesting an involvement of miR-132 in spatial memory formation. However, mice expressing miR-132 above the physiologically relevant level unexpectedly performed worse in the novel object recognition task [54,62] and the Barnes maze [62]. Excessive spine growth might be one of the side-effects of transgenic miR-132 overexpression that might limit the functional working range of neurons [62].…”
Section: (I) Mir-132mentioning
confidence: 99%
See 2 more Smart Citations
“…Mir-132 levels in the hippocampal formation are also increased by other behavioural tasks, such as the Barnes maze or novel object recognition [62], suggesting an involvement of miR-132 in spatial memory formation. However, mice expressing miR-132 above the physiologically relevant level unexpectedly performed worse in the novel object recognition task [54,62] and the Barnes maze [62]. Excessive spine growth might be one of the side-effects of transgenic miR-132 overexpression that might limit the functional working range of neurons [62].…”
Section: (I) Mir-132mentioning
confidence: 99%
“…B 369: 20130515 acquisition, because virus-mediated inhibition in vivo leads to an impairment in the storage of temporally associated information [61]. Mir-132 levels in the hippocampal formation are also increased by other behavioural tasks, such as the Barnes maze or novel object recognition [62], suggesting an involvement of miR-132 in spatial memory formation. However, mice expressing miR-132 above the physiologically relevant level unexpectedly performed worse in the novel object recognition task [54,62] and the Barnes maze [62].…”
Section: (I) Mir-132mentioning
confidence: 99%
See 1 more Smart Citation
“…3A). In addition, to gain an even greater level of insight into the roles of these miRNAs in sculpting the gene expression in the hippocampus, we also performed high-throughput RNA-seq in mice that transgenically overexpress either miR-132 (Descried in Hansen et al 2010Hansen et al , 2013 or a newly generated miR-212 transgenic mouse line (Figs. 3B, 4).…”
Section: Cognitive Impairment Following Targeted Deletion Of Mir-132/mentioning
confidence: 99%
“…To date, a number of studies have shown that both miRNAs are associated with impaired cognition when their expression levels are not maintained within a tightly regulated range (Scott et al 2012;Wang et al 2013;Kempf et al 2014). Moreover, while moderate overexpression (approximately fivefold increase) of miR-132 impairs learning and memory, small increases ( 1.5-fold) serve to facilitate performance on memoryassociated behavior tasks (Hansen et al 2013). This suggests that there exists an optimized level of miR-132 expression that can facilitate cognition, but that deviation from this range impairs neuronal function (Mellios et al 2011;Tognini et al 2011;Tognini and Pizzorusso 2012;Hansen et al 2013).…”
mentioning
confidence: 99%